Offering Clinical Pharmacy Clerkship in Hospital for Pharmacy Student: A Successful Cooperation between Medical and Pharmacy Schools - Kaveh Eslami; Mina Khezrian; Mohsen Rezaei; Leila Kouti (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Pharmacy education has been changed in recent years. Pharmacy students need more practical and clinical skills which come from direct interaction with patients and other health care providers. To achieve this, students need more effective courses and clerkships. In this paper we describe our method to design and evaluate clinical pharmacy clerkship for the first time in Ahvaz Jundishapur University of Medical Sciences (AJUMS). Methods: To  determine  the  most  beneficial way  of  education  we  designed  a  pilot  study  in educational hospital of AJUMS. After analyzing the conclusions from pilot study, 40 fifth year pharmacy student divided in ten groups and each group had a six week rotation in three different wards under supervision of medical residents. Each student was asked to provide evaluations during six total weeks of three different rotation sites. Results and Discussion: Clinical pharmacy clerkship led to successfully improved clinical skills for students such as being familiar with different practice environments, direct communication whit patients and medical team and participation in direct patient care activities. All the students participate in the course could pass the final exam and 85% of students believed this would be a necessary education course in their clerkship programs. Although there were some problems but pharmacy students benefited from this course and it gives them advantages in clinical knowledge and professional communication skills.